Service Quality Gap of Rural Customers Towards Banking Services in Karur Vysya Bank of Virudhunagar District - C.Sam Stephen, S.Karthik (Journal of Informatics Education and Research, 2024)
There are many villages in India, but they are not developing as quickly as the cities. Because of the lack of technology availability and infrastructure and other factors, customers in rural and urban areas have very different expectations and perceptions of products and services. Using the SERVQUAL test, we aim to determine the KVB rural customers' expectations and perceptions of service quality. Service quality expectations and perceptions differ from person to person and bank to bank. Service quality leads to customer retention and prospective customer base. We discovered that there is a big gap between the rural customer’s expectation and perception. Further we provide suggestion to karur vysya bank to put research and development team among rural customers and improve the bank services accordingly.